2014
DOI: 10.1017/ice.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between National Healthcare Safety Network Laboratory-Identified Event Reporting versus Traditional Surveillance for Clostridium difficile Infection

Abstract: Objective Hospitals in the National Healthcare Safety Network began reporting laboratory-identified (LabID) Clostridium difficile infection (CDI) events in January 2013. Our study quantified the differences between the LabID and traditional surveillance methods. Design Cohort study. Setting A cohort of 29 community hospitals in the southeastern United States. Methods A period of 6 months (January 1, 2013, to June 30, 2013) of prospectively collected data using both LabID and traditional surveillance defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
2
13
2
Order By: Relevance
“…Fewer studies reported overall rates of hospital- and community-acquired CDI. Nevertheless, the current literature suggests that hospital-onset CDI in Japan occurs at an incidence of 0.8–4.7 cases/10,000 patient-days; lower than that reported in Europe for winter 2012–2013 (country range 0.7–28.7/10,000 patient bed-days), and similar to the US for hospital-onset CDI in 2013 (6.0/10,000 patient-days for laboratory-identified CDI and 4.4/10,000 patient-days for traditional surveillance-detected CDI) [ 54 , 55 ]. However, direct comparisons between studies are difficult owing to differences in design, population size and detection methods used.…”
Section: Discussionmentioning
confidence: 78%
“…Fewer studies reported overall rates of hospital- and community-acquired CDI. Nevertheless, the current literature suggests that hospital-onset CDI in Japan occurs at an incidence of 0.8–4.7 cases/10,000 patient-days; lower than that reported in Europe for winter 2012–2013 (country range 0.7–28.7/10,000 patient bed-days), and similar to the US for hospital-onset CDI in 2013 (6.0/10,000 patient-days for laboratory-identified CDI and 4.4/10,000 patient-days for traditional surveillance-detected CDI) [ 54 , 55 ]. However, direct comparisons between studies are difficult owing to differences in design, population size and detection methods used.…”
Section: Discussionmentioning
confidence: 78%
“…12,[21][22][23] Other studies have pointed out inaccuracies in the LabID classification of CDI events, HO-CDI risk adjustment for C. difficile test method and SIR calculation. 8,[24][25][26][27] Our study adds unique information by demonstrating that failure to adjust for important high-risk patient populations in general acute-care hospitals may lead to falsely elevated SIR results.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, the variation of di↵erent CDI definitions within the literature is also reflected in surveillance methods used in practice to measure incidence of HA CDI. Research has shown that traditional surveillance methods, which use a 48 hour window to define HA cases, and the laboratory-identified method used by the National Healthcare Safety Network, which uses a 72 hour window, can produce dramatically di↵erent results when ranking hospitals based on their incidence of HA CDI [48]. Therefore, when analyzing and comparing results across studies and hospital surveillance reporting, it is important to pay attention to the various inclusion criteria used when defining di↵erent CDI cases.…”
Section: Classification Of CDI By Source and Occurrence Of Symptomsmentioning
confidence: 99%
“…Due to the increasing incidence and growing costs associated with HAIs, many Network also began reporting CDI events [129,48]. Given this increased availability of public information on hospital incidence of HAIs, studies have now begun using hospital incidence rates of HAIs, such as MRSA and CDI, as measures for making hospital-level comparisons [30,151].…”
Section: Hospital Reporting and Comparison Of CDI Incidencementioning
confidence: 99%
See 1 more Smart Citation